Analysis of PVC-based Product Inventory Control with Economic Production Quantity and Lagrange Multiplier Methods at PT. XYZ - Fitroni, Mochammad Rafqy Al; Pulansari, Farida (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT XYZ is a manufacturing company that produces various kinds of products made from PVC (Polyvynil Chloride). Some of the PVC-based products produced by PT XYZ are transparent sheet, colour sheet, and flooring. The problem that exists at PT XYZ is that the company often produces more than the amount of demand which makes the company have to prepare a storage warehouse with a capacity as large as the number of products produced. With this, the storage warehouse experiences overcapaity in controlling the inventory of products produced by the company. And it can be concluded that the problem that occurs at PT XYZ is inventory control and production quantity planning that has not been well planned. Based on the problems that occur at PT XYZ, the most suitable method used to solve these problems is the Lagrange Multiplier method. This research has a purpose to control the inventory of products made from PVC so as to minimize the total cost of product inventory at PT. XYZ. From the research This study found the optimal production amount of 1,332,999 m. Where with the amount of production, the company needs a warehouse area of 9,299.9 m3. The total inventory cost calculated using the Lagrange Multiplier method is IDR 377,073,841,401 while the company's total inventory cost is IDR 402,844,596,680. So that a savings of IDR 25,770,755,279 or 6.40% is obtained.